Community empowerment : a new approach or participation in disguise? : a thesis presented in part fulfilment of the requirements for the degree of Master of Philosophy in Resource and Environmental Planning, Massey University - Barrett, P. J. (Massey University, 1995)
This thesis provides a theoretical conceptualisation of a process that links international community empowerment strategies with community empowerment approaches and attributes at various political levels. The thesis has derived a theoretical set of guiding community empowerment attributes form current community empowerment approaches. Guiding attributes may provide a means of understanding of current actions by which community empowerment is being implemented. Guidelines may also be used as criteria for the evaluation of existing community empowerment approaches in terms of more democratic decision making. In addition, guidelines may be used to test the initial idea for the establishment of community empowered groups. A comparison and contrast of one New Zealand community empowerment programme with the theoretical set of guiding community empowerment attributes is made. The comparison and contrast shows that when a community empowerment approach incorporates and implements the majority of theoretical attributes, it may result in greater community participation, responsibility and more democratic decision making at the community level. Such community cooperation has advantages for local authorities in the management of natural and physical resources.
Keywords: Community development; Community organization